Emphysematous cystitis: An atypical multi-organism presentation - Bos, Derek; Patal, Premal; DiTullio, Sonia (Canadian Urological Association Journal, 2014)
An 84-year-old diabetic women receiving in-hospital strokemanagement began suffering from vague lower abdominal pain,increased urge incontinence and gross hematuria. Physical examinationrevealed suprapubic tenderness and a tympanic bladder.A computed tomography confirmed a distended bladder with gasfoci delineating the bladder wall. Microbiology revealed an atypicalmulti-organism presentation of Klebsiella pneumoniae andEnterococcus species. Emphysematous cystitis is characterized byair within the bladder wall often found in elderly diabetic females.Predominant organisms include Escherichia coli and Klebsiellapneumonia. Prompt treatment is essential in this potentially fatalcondition.